Caricom and humanitarian intervention : towards a legal response to the United Nations Secretary-General - Vasciannie, Stephen (2003)
Looks at UN Secretary-General Kofi Annan's vision of a new legal and political order concerning the use of force in international relations. Notes his support for the doctrine of humanitarian intervention. Examines some of the factors that should inform a CARICOM response to the Secretary-General's position.